H06 Longitudinal Psychiatric Symptoms in Premanifest HD: Psychiatric Progression and Unawareness in a Decade of Data. (17th September 2014) - Miller, A; Epping, E; Kim, J; Long, JD; Brashers-Krug, T; Craufurd, D; Paulsen, J
Abstract : Background: Huntington Disease (HD) is an autosomal dominant neurodegenerative disease that typically manifests with motor, cogniti1ve and psychiatric symptoms. The majority of research emphasises the motor and cognitive phenotype of HD. Cross-sectional research consistently shows increased psychiatric and behavioural impairments in HD although few studies have examined longitudinal changes in psychiatric symptoms. Aims: Here we report longitudinal behavioural data with up to ten years of follow-up to identify behavioural changes that occur in premanifest HD up to and through motor conversion. Methods: Using the Symptom Check List-90-Revised (SCL90), a 90-item self-report scale of psychological symptomatology, we analysed data from 1305 participants (cases and controls) with 6112 observations and their 1235 companions with 5365 observations. Individuals with CAG repeat expansion (CAG≥36) served as cases while people who tested negative for the expansion (CAG <36) were controls. Participant and companion ratings were analysed separately using linear mixed effects regression (LMER). The time metric was duration, defined as time since study entry in years. Results: Of the 24 psychiatric outcome variables examined, 19 showed significant baseline and longitudinal differences between cases and controls. Further, when analyses were conducted to examine ratings between cases and companions, findings showed inconsistency between the raters that is interpreted in terms of unawareness associated with HD progression. Conclusions: In cases near motor onset, companion ratings appear to be more valid than patient-report. Our findings indicate that unawareness increases in concert with disease progression during premanifest stages. Psychiatric disturbances demonstrate worsening over time in concert with disease progression in HD.